Peace studies in the Chinese century: international Perspectives - Hunter, Alan (ed.) (England, 2006)
The rise of China is probably the most significant shift in the international power structure this generation. China's leaders have so far committed themselves to a 'peaceful rising' but serious tensions are inevitable in such a rapid transformation. Dialogue on peace and conflict issues at this juncture is invaluable. This volume focuses on developments in peace research in a number of key countries, and in particular introduces for the first time in English the perspectives of a number of Chinese scholars who have started to engage with peace studies agendas. Comparisons are drawn from the UK, USA, Mexico, Japan and South Africa to provide a better understanding of the debates on a global level and the discussion among different countries. Some of the outstanding peace researchers who contribute to the volume include Andrew Rigby, Johan Galtung - who is generally considered to have founded the discipline in its current form - and Ursula Oswald. The volume is a valuable and unique contribution to the contemporary peace research agenda and will appeal to an interdisciplinary readership in peace studies, sociology, politics, international relations, religious studies, philosophy and Asian studies.
Keywords: Peace-building-China